Can tests of physical fitness predict traumatic knee injury in youth female athletes? A prospective cohort study - Augustsson, S. R.; Gustafsson, T.; Ageberg, E. (Physical Therapy in Sport, 2024)
Objectives To compile a battery of test including various aspects of physical fitness that could be used on the field and to assess whether any of these tests are associated with future traumatic knee injuries in youth female team sports athletes.